Regenerative and Anti-Senescence Potential of Extracts from Different Parts of Black Persimmon in an In Vitro Model of Vascular Endothelium - Graziella Serio; Sina Naserian; Sawssen Ben Fraj; Georges Uzan; Carla Gentile (Foods)
Antioxidants are essential for mitigating oxidative stress and maintaining vascular health. Endothelial colony-forming cells (ECFCs) are pivotal in endothelial regeneration and angiogenesis and serve as a model to study the diversity of endothelial cells across various organs. This study evaluated the effects of peel, pulp, and seed extracts from Diospyros digyna Jacq. fruit (black persimmon) on human cord blood-derived ECFCs (CB-ECFCs) to determine how the distinct antioxidant profiles of the fruit’s different parts influence cellular functions. The extracts did not affect endothelial marker expression, cell proliferation, or nitric oxide production, indicating no cytotoxic or inflammatory effects. However, functional assays revealed that the seed extract significantly enhanced tube formation, increasing closed tubular networks by 1.5-fold. All extracts promoted cell migration, with the seed extract demonstrating the most substantial effect, surpassing even vascular endothelial growth factor (VEGF). Additionally, the seed extract exhibited the strongest reduction in cellular senescence, both before and after oxidative stress induction with H2O2. These findings underscore the potential of black persimmon extracts, especially from the seed, to enhance the regenerative capabilities of CB-ECFCs and reduce cellular senescence without affecting the normal endothelial phenotype. This positions them as promising candidates for developing endothelial cell therapies and advancing vascular regeneration.